Extracorporeal Membrane Oxygenation Can Successfully Support Patients With Severe Acute Respiratory Distress Syndrome in Lieu of Mechanical Ventilation. Issue 11 (November 2018) - Kurihara, Chitaru; Walter, James M.; Singer, Benjamin D.; Cajigas, Hector; Shayan, Shahriar; Al-Qamari, Abbas; DeCamp, Malcolm M.; Wunderink, Rich; Budinger, GR Scott; Bharat, Ankit
Abstract : Objectives: Extracorporeal membrane oxygenation is increasingly used in the management of severe acute respiratory distress syndrome. With extracorporeal membrane oxygenation, select patients with acute respiratory distress syndrome can be managed without mechanical ventilation, sedation, or neuromuscular blockade. Published experience with this approach, specifically with attention to a patient's respiratory drive following cannulation, is limited. Design: We describe our experience with three consecutive patients with severe acute respiratory distress syndrome supported with right jugular-femoral configuration of venovenous extracorporeal membrane oxygenation without therapeutic anticoagulation as an alternative to lung-protective mechanical ventilation. Outcomes are reported including daily respiratory rate, vital capacities, and follow-up pulmonary function testing. Results: Following cannulation, patients were extubated within 24 hours. During extracorporeal membrane oxygenation support, all patients were able to maintain a normal respiratory rate and experienced steady improvements in vital capacities. Patients received oral nutrition and ambulated daily. At follow-up, no patients required supplemental oxygen. Conclusions: Our results suggest that venovenous extracorporeal membrane oxygenation can provide a safe and effective alternative to lung-protective mechanical ventilation in carefully selected patients. This approach facilitates participation in physical therapy and avoids complications associated with mechanical ventilation.